The Prevalence and Outcome of Bile Spillage during Elective Laparoscopic Cholecystectomy (Journal of Society of Surgeons of Nepal, 2022)
Introduction: Laparoscopic cholecystectomy (LC) has a low risk for postoperative infective complications. The incidence of iatrogenic gall bladder perforation leading to spillage of bile and stones seems to be higher ranging between 5 and 40%. Studies have also shown an increased incidence of complications like surgical site infection (SSIs) after bile spillage. This study aims to assess the prevalence and outcome in bile spillage during LC.Methods: A cross-sectional study was conducted at KIST Medical College and Teaching Hospital. All the patients who underwent elective LC from February 2018 to March 2020 were studied. A total of 187 patients were enrolled. The required data was entered in the proforma by reviewing the patient’s medical records. The data was entered and analyzed using the SPSS version 26. Descriptive statistics and chi-square test were carried out.Results: The prevalence of bile spillage was 29.4%. The prevalence of SSIs among the bile spillage and non-bile spillage groups was 10.9% and 8.3% respectively. There was no significant association between SSIs and bile spillages (p value 0.584). There is no significant association post operative use of antibiotics and SSIs among patients with bile spillage (p value = 0.163).Conclusion: The prevalence of bile spillage during LC was higher when compared to other national and international studies. However, the rate of SSIs among bile spillage was lower. Bile spillage during LC doesn’t cause SSIs post-operatively and use of postoperative antibiotics among bile spillage patients doesn’t prevent SSI during elective LC thus use of antibiotics in such cases should be limited.